Submerged and non-submerged 3D bioprinting approaches for the fabrication of complex structures with the hydrogel pair GelMA and alginate/methylcellulose - Li, Huijun (2021)
The extrusion-based bioprinting of hydrogels such as gelatin methacrylate (GelMA) into structures with complex shape suffers from poor printability due to their low viscosity. The present study deals with hydrogel materials by using the mixture of cell-laden photopolymerizable GelMA as a main printing material and the mixture of alginate and methylcellulose (Alg/MC) as a support material because of its high viscosity and good thixotropic property. One extrusion-based approach is developed by printing the two mixtures into structures in an alternating layer-by-layer manner, with the electrostatic interactions between polycationic GelMA and polyanionic Alg/MC contributing to the integrity of the structures. The final printed structures are exposed to ultraviolet (UV) light to form crosslinks in GelMA through photopolymerization for further structural strengthening. The one-time UV exposure minimizes cell damage in cell-GelMA, demonstrating an advantage over those in previously reported studies that required repeated UV exposures upon the printing of each layer of a structure. The other approach is developed by submerging the extrusion nozzle into a bath of Alg/MC to print cell-laden GelMA structures, which, upon printing completion, are also subject to one-time UV exposure before the removal of the support material Alg/MC. A flower with living cells is printed to demonstrate the capability of the second approach of fabricating structures with geometric complexity. The structures printed using both approaches demonstrate a well-maintained shape fidelity, structural integrity and cell viability of over 93% up to five culturing days. The proposed two printing approaches based on the cell-GelMA and Alg/MC pair will be beneficial for exploring new opportunities in bioprinting.